Drenaje postural, su incidencia en la fibrosis pulmonar de adultos mayores del recinto la teresa Babahoyo Los Ríos, periodo septiembre 2017 a febrero 2018. - Litardo Cordova, Juan Carlos (2018)
Pulmonary fibrosis is a disease that occurs when lung tissue is damaged and scarring occurs. This thickened and rigid tissue makes it harder for your lungs to function properly. As lung fibrosis gets worse, you have more and more difficulty breathing. The damage to the lungs caused by pulmonary fibrosis can not be repaired, but medications and therapies can sometimes help relieve symptoms and improve quality of life. This disease affects men more than women and is usually diagnosed in adulthood between 50-80 years. The evolution and severity of symptoms can vary considerably from one person to another. Some get sick quickly and have a serious condition. Others have moderate symptoms that worsen more slowly, over the course of months or years. There are many substances and conditions that can cause pulmonary fibrosis. The average survival is three to five years from diagnosis. Natural history is a progressive deterioration, but there are fast forms and exacerbations can also appear that overshadow the prognosis